Meta-Analysis the Effect of Malaria Infection on Anemia in Pregnant Women - Firdausi Nuzula; Setyo Sri Rahardjo; Bhisma Murti (Journal of Epidemiology and Public Health, 2020)
Background: Malaria is an important threat to pregnant women, with an increased risk for both mother and newborn, especially in the first and second pregnancies caused by P. falciparum. Malaria infection in pregnant women can cause anemia in the mother and fetus, as well as babies with low birth weight, this can increase maternal and infant mortality rates. This study aims to analyze the magnitude of the influence of malaria infection in pregnant women on the incidence of anemia based on a number of previous similar studies.Subjects and Method: This was a systematic review and meta-analysis carried out by following the PRISMA flow diagram. The process of searching for articles is carried out through a journal database which includes: Google Scholar, PubMed, and Science Direct by selecting articles published in 2010-2020. Key words used include: "malaria infection" AND "pregnancy women" OR "anemia" AND "adjusted odds ratio". The inclusion criteria were full paper articles with observational study design, articles in English, multivariate analysis used with adjusted odds ratios. Articles that meet the requirements are analyzed using the Revmen 5.3 application.Results: A total of seven articles were reviewed in this study with a cross-sectional study design. A meta-analysis of 7 cross-sectional studies showed that malaria infection had a 1.72 times increased risk of anemia in pregnant women compared to those not infected with malaria (aOR 1.72; 95% CI 1.43 to 2.07; p <0.001).Conclusion: Malaria infection increases the risk of anemia in pregnant women.Keywords: malaria infection, pregnancy, anemia, meta-analysisCorrespondence: Firdausi Nuzula. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ulafn10@gmail.com.Journal of Epidemiology and Public Health (2020), 05(04): 489-498https://doi.org/10.26911/jepublichealth.2020.05.04.11